Gambaran pengelolaan sampah padat pada pedagang di pasar Karuwisi kota Makassar - Syatriani, Sri; Silwanah, Andi Sani; Baersady, Margaretha M. (EcoVision: Journal of Environmental Solutions, 2024)
Waste is an object, whether solid or liquid, that is no longer used and is simply thrown away by the owner. According to the World Health Organization (WHO), waste is something that is no longer wanted, not used, not liked or something that is thrown away that comes from human activities and does not occur by itself. The volume of waste generation in Indonesia in 2022 will reach 19.45 million tons. This figure decreased by 37.52% from 2021 to 31.13 million tons. Aim to determine the sorting, collection, and transportation of solid waste by traders. The type of research is descriptive research. The population and research sample were all 79 traders in the Karuwisi market. Sampling used a total sampling technique with a sample size of 79 traders. Data was collected using interview and observation methods using questionnaires and observation sheets. More people did not meet the requirements for waste sorting, namely 40 people (50.6%) than those who met the requirements. There were more people collecting waste who did not meet the requirements, namely 47 people (59.5%) than those who did, while all waste transporters met the requirements, namely 79 people (100%). The management of solid waste among traders in the Karuwisi market in Makassar City still does not meet the requirements, most traders do not sort waste, most traders also do not collect waste, and the transportation of waste at the Karuwisi market is very good, the tools used to collect it trash like dump trucks. It is recommended that traders at the Karuwisi market sort waste and collect waste according to its type.